Implementation of Mediation As Online Dispute Resolution (ODR) in Civil Jurisdiction - Bambang SUTIYOSO (Indonesia Strategic Sustainability, 2023)
This writing aims to examine and analyze business/civil dispute resolution through online dispute resolution (ODR), institutionalization of mediation in civil cases in court, implementation of mediation as online dispute resolution (ODR) in civil courts, obstacles and legal implications for parties - the litigants. Mediation as an alternative dispute resolution mechanism outside the court has long been used in various business and civil cases, the environment, labor, land, housing, consumer disputes, and so on which is a manifestation of society's demand for fast, effective and efficient dispute resolution. The issuance of Perma Number 1 of 2016 concerning Mediation Procedures in Courts and Perma Number 3 of 2022 concerning Electronic Mediation in Courts further strengthens efforts to reconcile as stipulated in Article 130 HIR/154 Rbg. Even so, dispute resolution through mediation in court is actually a vulnerable mechanism, meaning that the possibility of failure is also very large. Anticipating this requires prerequisites that must be met, such as trust, willingness or willingness to waive some of the rights of each party to the dispute, and the availability of a professional mediator. Â